The Theatrical Laboratory as Critical Training Ground for Democracy: Pedagogical Reflections and a Historical Example - Elisabetta Villano (Pensa MultiMedia, 2022)
In order to respond to the crisis of the last two years in a proper way, a paradigm shift seems necessary to centralize the individual and collective active responsibility in transformative and generative processes for a new start and change. The pedagogical (re)centralization of the person as change agent entails an education whose objective is the emancipation of man, caught in the relationship between the particular and the universal. Starting from here, this study aims to explore a possible democracy-oriented political education modality, which enables to grasp the contemporary complexity from a critical perspective. The starting point will be the pedagogical thought of Klaus Mollenhauer, then a different realization space - the theatrical laboratory - will be proposed, in the light of some pedagogical studies about the connection between theatre and education and considering the historical experience of the Schaubühne am Halleschen Ufer in Berlin, directed by Peter Stein from 1970.